Bachelor of Quantity Surveying (Honours) UNIMAS - Atta Idrawani, Zaini; Sitti Diana, Tamjehi; Afzan, Ahmad Zaini; Gui, Hun Chuen; Abdul Wafi, Razali (YouTube, 2020)
A 2-min promotional video of Bachelor of Quantity Surveying (Hons) which is offered by the Department of Quantity Surveying, Faculty of Built Environment UNI...